Production Of Flavonoid, An Anti-Inflammatory Agent From Trametes lactinea - Yahaya, Yus Azila (2014)
Flavonoid is one of the remarkable bioactive compound that possesses broad pharmacological activities including anti-inflammatory. A simple and effective bioroute approach for the production of flavonoid by six locally isolated strain obtained from culture collection center were looked at. Flavonoid adalah salah satu sebatioan bioaktif yang berharga dan mempunyai aktiviti farmakologi yang luas termasuk anti-radang. Pendekatan ke arah biologi yang mudah dan berkesan bagi menghasilkan flavonoid dari enam spesies tempatan yang telah dipencil dan diperolehi daripada pusat pengumpulan kultur telahpun dijalankan.